Seismic vulnerability of buried pipelines - Xiangyue Li Liu; Raúl Flores-Berrones (Geofísica Internacional, 2003)
Earthquakes may cause severe damage to buried pipelines. One dramatic example occurred during the Michoacán earthquakes of September 1985. Many aqueducts and pipelines in Mexico City and in Lázaro Cárdenas failed as a result of those earthquakes. Similar damages were also observed more recently in the earthquakes in Loma Prieta (Marina District), in 1989; in Northridge, California in 1994; and in Kobe, Japan, in 1995.This paper illustrates the kind of problems that take place after the failure of pipelines conducting water, gas or sewage. It also gives the principal causes of those failures, and the methods available today to take into consideration seismic effects for the proper design of buried pipelines. Some simplified procedures for preventing effects due to permanent ground deformation and seismic wave propagation on continuous and segmented pipelines are given, together with some recommendations to be followed when installing buried pipelines in seismic areas.